2020
DOI: 10.1093/cid/ciaa574
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Profile of Laboratory Parameters and Their Application in the Prediction for Fatal Outcome Among Patients Infected With SARS-CoV-2: A Retrospective Cohort Study

Abstract: Background Patients with coronavirus disease 2019 (COVID-19) experience a wide clinical spectrum, with over 2% developing fatal outcome. The prognostic factors for fatal outcome remain sparsely investigated. Methods A retrospective cohort study was performed in a cohort of patients with confirmed COVID-19 in one designated hospital in Wuhan, China, from 17 January–5 March 2020. The laboratory parameters and a panel of cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
2
13
0
1
Order By: Relevance
“…There was a strong negative correlation between IL-6, IL-10 and total lymphocytes, T lymphocytes, CD4 + T cells, CD8 + T cells and NK cells. Lymphopenia was observed in most of the critical cases with COVID-19 on admission and could be a potential predictor for prognosis, as reported in recently published studies [8,[16][17][18]. Further analysis of the lymphocyte subsets also showed a significant decline in T lymphocytes, CD4 + T cells, CD8 + T cells, B cells, and [1], up-regulation of apoptosis and autophagy in lymphocytes [19], lung tissue recruitment of immune cells [20] and destruction of lymphatic organs, including the spleen and lymph nodes [21].…”
Section: Discussionsupporting
confidence: 59%
“…There was a strong negative correlation between IL-6, IL-10 and total lymphocytes, T lymphocytes, CD4 + T cells, CD8 + T cells and NK cells. Lymphopenia was observed in most of the critical cases with COVID-19 on admission and could be a potential predictor for prognosis, as reported in recently published studies [8,[16][17][18]. Further analysis of the lymphocyte subsets also showed a significant decline in T lymphocytes, CD4 + T cells, CD8 + T cells, B cells, and [1], up-regulation of apoptosis and autophagy in lymphocytes [19], lung tissue recruitment of immune cells [20] and destruction of lymphatic organs, including the spleen and lymph nodes [21].…”
Section: Discussionsupporting
confidence: 59%
“…This result is in accord with Zhou et al’ 8 study indicating that the level of hs-cTnI increased significantly from 10 to 13 days after symptoms onset in COVID-19 patients. Similar to the results of a longitudinal study 17 , the patients in the second week after symptoms onset had the highest levels of CRP and LDH, which could be considered as the signs of the systemic inflammatory response. Moreover, in line with a previous study 3 , our results demonstrated that the cardiac biomarkers were highly related to lymphocyte count and CRP, suggesting that cardiac damage of COVID-19 was related to viral response and hyperinflammation.…”
Section: Discussionsupporting
confidence: 82%
“…Later, Zhang et al 17 and Levy et al 18 concluded that NEU and CRP were predictive factors of in‐hospital death. Furthermore, IL‐6 was considered to be an incredibly important prognostic factor for COVID‐19‐related death 19–21 . Herein, we integrated the three indicators into a nomogram, resulting in satisfactory performance.…”
Section: Discussionmentioning
confidence: 99%